2018
DOI: 10.1155/2018/7234101
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression in Chinese Medicine Outpatients with Stagnation Syndrome: Prevalence and the Impairments in Well‐Being

Abstract: Stagnation syndrome, a diagnostic entity in traditional Chinese medicine (TCM), has been long regarded as the TCM counterpart of major depression in Western medicine. The study investigated the prevalence of major depression among stagnation syndrome patients and evaluated their well-being and functioning outcomes. In total, 117 patients diagnosed with stagnation syndrome were measured using Stagnation Scale, the Patient Health Questionnaire-9 (PHQ-9), and the Body-Mind-Spirit Well-Being Inventory. Results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Western drugs effectively manage PDD but are associated with side effects and decreased quality of life [ 13 – 15 ]. TCM can be combined with western drugs for depressive disorders [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Western drugs effectively manage PDD but are associated with side effects and decreased quality of life [ 13 – 15 ]. TCM can be combined with western drugs for depressive disorders [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medication is still the primary treatment method [ 1 , 11 , 12 ]. Traditional Chinese medicine (TCM) can also be used to manage PDD [ 13 – 15 ]. Both TCM and western medicine have certain curative effects, but each has advantages and disadvantages [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stagnation Syndrome includes depression, restlessness, emotional changes, lack of energy, frequent sighing, and poor appetite (97,98). Leng et al (99,100) suggested that Stagnation Syndrome was related to MDD and functional somatic syndrome, because Stagnation Syndrome showed various bodily symptoms and psychological problems.…”
Section: Necessity For New Anger Disordermentioning
confidence: 99%